An insight into the present capabilities of national metrology institutes for measuring sparkle. (5th November 2020) - Ferrero, A; Basic, N; Campos, J; Pastuschek, M; Perales, E; Porrovecchio, G; Šmid, M; Schirmacher, A; Velázquez, J L; Martínez-Verdú, F M
Abstract: Large-effect pigments, due to their strongly specular reflectance, produce a special visual texture known as sparkle. The use of these pigments in many industries (automotive, cosmetic, paper, architecture...) makes the control of this visual texture necessary. Sparkle measurands have been defined in this article, so that traceability of sparkle measurements can be provided by national metrology institutes or designated institutes. Some of them (Physikalisch-Technische Bundesanstalt, Eidgenössisches Institut für Metrologie, Cesky Metrologicky Institut and Consejo Superior de Investigaciones Científicas) have tested their existing measurement capabilities for the defined sparkle measurands, and their results are presented and thoroughly compared. Two possible sources of systematic error have been identified: inadequate illumination and collection solid angles, and an inadequate size of the virtual aperture used to assess the luminous flux reflected by the effect pigments. Finally, it has been shown that the measures correlate excellently with the sparkle visual data. The results shown in this research support the sparkle measurands defined here as adequate quantities for defining the standard measurement scale of sparkle claimed by industry.